Tiktok for Adlab's Brand Awareness - Wicaksono, Apriansyah; Priyandhini, Besty (Jurnal Vokasi Indonesia, 2024)
Currently, social media has become a communication tool that exists in almost every aspect of life. Social Media marketing has become a form of marketing that is very relevant with advances in social web technology. A Social Media Specialist has an important role in increasing the existence of a TikTok account to expand the brand awareness. The focus of this thesis is to highlight the role of Social Media Specialists in developing TikTok Adlab UI brand awareness, outline the message to form Adlab brand awareness, and describe the content strategy implemented. The methodology used in this writing includes observation and interviews as primary methods and literature study as secondary methods. Adlab UI, is an advertising agency based on collaboration between practitioners and academics from the Creative Advertising Study Program, Vocational Education Program, Universitas Indonesia. As a Social Media Specialist at Adlab, the main duties include content planning, ideation, production and regular evaluation of TikTok content. This role also includes developing TikTok content plans, ideation, production, and reporting on TikTok Adlab's social media progress. In order to expand the brand awareness, the Social Media Specialist is also responsible for content management and content pillars. During the period April to May 2024, the Social Media Specialist has posted 10 contents whilst implementing a new strategy by introducing the hashtag #LifeatAdlab to strengthen Adlab's brand awareness. The content strategy that Adlab has implemented has proven effective in expanding brand awareness, as well as making a significant contribution to the overall growth of Adlab's TikTok account.